Health Insurance Demand Dynamics: Factors Influencing Individual And Family Decisions In Purchasing Insurance - Trinarsih Trinarsih; Ilma Widia Hadi; Anah Farkhanah; Erlina Puspitaloka Mahadewi (CV. Inara, 2025)
The study focused on the purpose of this writing is to find out the importance of study examines the dynamics of health insurance demand in Indonesia now, with more focusing on the factors that influence individual and family decisions to purchase insurance policies after the pandemic. Through an in-depth literature analysis, this study explores various economic, social, and policy aspects that contribute to the level of health insurance penetration in a developing country like Indonesia today. Based on a qualitative approach, this study examines how income, education level, and awareness of health risks interact to shape consumer behavior. In addition, this study also considers the impact of government programs and private initiatives in increasing ease of access to health insurance. The results show that there is a significant relationship between the level of financial and health literacy, with the tendency to take and or purchase health insurance. In addition, perceptions of service quality, and trust in insurance service providers are also proven to play an important role in the future. This study provides recommendations for policy makers and industry practitioners to design more effective strategies, in increasing health insurance coverage. This study is expected to contribute to collective efforts to achieve Universal Health Coverage (UHC) in Indonesia soon in the best possible way.